Study on the Design of the VFR (Visual Flight Rules) Corridor Connecting Airports in North Sumatra Province - Inda Tri Pasa; Liber Tommy Hutabarat; Ivana Wardani; Fauziah Nur; Maulana Chairul Muchlisin; Agung Pramono (Riviera Publishing, 2024)
This research aims to design a VFR Corridor that can connect airports located in the province of North Sumatra, especially those airports that do not yet have a VFR Corridor. The research method used is Research and Development (R&D). Data was collected using observation, literature study, interviews, and documentation. The results showed that the current condition of the VFR Corridor has not connected the eight airports in the North Sumatra region. However, the eight airports can be connected with the new VFR Corridor design consisting of three segments. This design allows VFR aircraft to follow the VFR Corridor path rather than flying direct. In addition, the VFR Corridor design also ensures that the movement of VFR aircraft will not interfere with IFR aircraft following STAR at Kualanamu Airport in Medan and Sisingamangaraja Airport. This study has implications for improving the safety and efficiency of flight operations in the North Sumatra region. With a structured and connected VFR Corridor, VFR aircraft pilots have clearer guidance in air navigation, so the risk of collisions with IFR aircraft can be minimized. In addition, this design also supports the development of aviation infrastructure in North Sumatra, especially in facilitating connectivity between airports that do not yet have a VFR Corridor.